2023
DOI: 10.3390/plants12102034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ionotropic Receptor Gene EonuIR25a in the Tea Green Leafhopper, Empoasca onukii Matsuda

Abstract: Ionotropic receptors (IRs) play a central role in detecting chemosensory information from the environment and guiding insect behaviors and are potential target genes for pest control. Empoasca onukii Matsuda is a major pest of the tea plant Camellia sinensis (L.) O. Ktze, and seriously influences tea yields and quality. In this study, the ionotropic receptor gene EnouIR25a in E. onukii was cloned, and the expression pattern of EnouIR25a was detected in various tissues. Behavioral responses of E. onukii to vola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Interestingly, EcorOrco −/− mutants of both male and female hoverflies still exhibited responses to several of the tested chemicals, such as 3-methyl-2-butenal and 2,3-butanedione (Figure 2C,D). This suggests that, in addition to the OR-dependent olfactory pathways, there may be other pathways in hoverflies, such as the ionotropic receptors (IRs), which play a role in recognizing these compounds [22]. This is consistent with studies in D. melanogaster, where single sensillum recording (SSR) recording showed that 2,3-butanedione not only activates ORs, but also elicits electrophysiological responses from IRs [23].…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, EcorOrco −/− mutants of both male and female hoverflies still exhibited responses to several of the tested chemicals, such as 3-methyl-2-butenal and 2,3-butanedione (Figure 2C,D). This suggests that, in addition to the OR-dependent olfactory pathways, there may be other pathways in hoverflies, such as the ionotropic receptors (IRs), which play a role in recognizing these compounds [22]. This is consistent with studies in D. melanogaster, where single sensillum recording (SSR) recording showed that 2,3-butanedione not only activates ORs, but also elicits electrophysiological responses from IRs [23].…”
Section: Discussionsupporting
confidence: 77%
“…PxylGR34 is a relevant receptor for the detection of brassinolide and 24-epibrassinolide in P. xylostella [37]. Previous studies showed that 63%, 70%, and 67% of E. onukii adults responded to phenylacetaldehyde at concentrations of 0.1, 10, and 100 µL/mL and were more attracted to phenylacetaldehyde at concentrations of 10 and 100 µL/mL [42]. After interference with EonuGR1 for 3 h, the responses to acetophenone decreased insignificantly, with no significant differences from the controls, and some decrease for 1-phenylethanol at 10 µL/mL, but no significant differences at other concentrations in E. onukii.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, olfactory responses of E. onukii to 1-phenylethanol, acetophenone, and phenylacetaldehyde were studied [42], and the results showed that the E. onukii adults were more attracted to volatiles, including phenylacetaldehyde at a concentration of 10 µL/mL, acetophenone as well as 1-phenylethanol at a concentration of 100 µL/mL. A Y-tube olfactometer was used to determine the behavioral changes of E. onukii in response to tea plant volatile compounds after interference with EonuGR1.…”
Section: Y-tube Olfactometer Assaysmentioning
confidence: 99%
“…RNAi referred to Zhang et al (2023) method. 34 EonuOBP43 was silenced by feeding dsEonuOBP43. The purified products, dsEo-nuOBP43, were thawed on ice, and the concentration was diluted to 1000 ng/μL.…”
Section: E Coli Expression and Purification Of The Recombinant Proteinmentioning
confidence: 99%